PENERAPAN METODE PROFILE MATCHING UNTUK MENENTUKAN PENULIS KARYA TULIS ILMIAH TERBAIK - Anisa Nurul Wilda, Anisa; Muhammad Edi Iswanto; Umi Diantika Susilowati (Department of Computer Engineering, Universitas Wiralodra, 2024)
Writing scientific papers is an annual agenda carried out by MA NU Assalafie for twelfth-grade students at the beginning of the odd semester. This activity is an effort by MA NU Assalafie to improve the competence of students, especially in terms of communication. Every student will be reporting the results of a book review they have read in the form of a paper, which throughout the process, every student will be accompanied by a teacher as a mentor who will guide them from the beginning of writing until the end when the student takes the scientific paper exam. Along the way, this activity will always produce the best scientific paper author, which is determined through the scientific paper writing exam. The problem that often arises from the decision-making process is the feeling of dissatisfaction from each examiner, as each examiner has a subjective view of the student being tested. To address this issue, in the 2022/2023 academic year, the decision-making process will be carried out by a subsection of the information system, namely the decision support system (DSS), using profile matching as the method used in the decision-making process. The implementation of DSS using profile matching produces the best alternative from a total of 139 students. Through usability testing using the system usability scale (SUS) method, the implementation of profile matching in determining the best student obtained a final score of 75, which means the system is acceptable to all parties involved. This is based on the fact that the implementation of profile matching can reduce the subjectivity of examiners in the process of determining the best student. In addition, the information generated by the DSS will be faster, more accurate, and accountable.